001 Altered interval timing as a novel marker of cognitive fluctuations in lewy body dementia. (29th July 2019) - Matar, Elie; Martens, Kaylena Ehgoetz; Phillips, Joseph; Halliday, Glenda; Lewis, Simon
Abstract : Introduction: Cognitive fluctuations are a core clinical feature of Dementia with Lewy Bodies(DLB), characterized by marked spontaneous variations in cognitive abilities and alertness. There is a paucity of objective measurements of fluctuations in the clinical setting. Altered time awareness represents a potential clinical marker of fluctuations and/or their severity. In this study we aimed to investigate qualities of interval timing in patients with DLB. Methods: 25 patients with probable DLB and 14 older controls underwent testing using a simple time perception paradigm testing probing different aspects of interval timing including time estimation(retrospective estimation of interval length), time production(prospective determination of an interval) and time pacing(explicit timing of an interval).Intervals of 10 to 90s were randomized between trials.Self/carer-reporting of fluctuations were measured using the clinician assessment of fluctuation(CAF) and one-day fluctuation(OFS) scales. Results: We found significant differences in interval timing between controls and DLB for time estimation and time production. Overall, DLB patients estimated less time which was significant at 90 seconds(proportion of interval=0.92 vs 0.69; p=0.03). DLB produced less time(proportion of 90s interval 0.58 vs 1.0; p<0.001). Errors in time estimation at 90 seconds correlated with fluctuation presence according to the CAF(r=0.47;p=0.009) whilst errors in time pacing at 90s correlated strongest with fluctuation severity according to the OFS(r=0.65, p<0.001). ROC analysis identified time production(90s) as a good test to distinguish DLB from controls (AUC=0.8;95%CI:0.75–0.98). Conclusion: We demonstrate objective evidence for altered temporal processing in DLB and suggest abnormal interval timing as a novel and clinically useful bedside marker of cognitive fluctuations.